Fairy tales of charles perrault ebook English and russian language edition. - Perrault, Charles (Children's Classics., 2015)
An iconic collection of fairy tales from the master of storytelling Charles Perrault including some of his best work: Little Red Riding-Hood, The Sleeping Beauty, Puss in Boots, Little Thumb, Cinderella, Blue Beard. This edition includes both English and Russian language texts.